Research on the integration path of physical training and police practical skills in police academy - Chen, Yun (Quality in Sport, 2025)
With the increasingly complex social security environment, public security education is facing higher requirements, especially in training high-quality law enforcement personnel to adapt to the complex police environment, how to optimize the training system has become a key issue. The organic integration of physical training and actual police skills is an important way to improve the comprehensive quality of public security team. However, at present, there is a common separation between the two kinds of training, which fails to fully reflect the practical value of mutual cooperation, thus restricting the training effect and the practical application ability of the students. In this study, the status quo and problems of physical training and actual combat skills training in the police academy education system are deeply analyzed, focusing on the necessity of the integration of the two and the implementation path. Through systematic theoretical analysis and practical exploration, a series of optimization schemes including scenario-based training, scientific physical fitness improvement strategy and integrated curriculum design are proposed. This study not only provides an important theoretical basis for the improvement of the education quality of the police academy, but also provides practical guidance for promoting the all-round development of the students and enhancing the effectiveness of law enforcement.